Paul Cuff. Abel Gance and the End of Silent Cinema: Sounding Out Utopia. Palgrave Macmillan, 2016. - Margaret C Flinn (Studies in 20th & 21st Century Literature, 2018)
Review of Paul Cuff. Abel Gance and the End of Silent Cinema: Sounding Out Utopia. London: Palgrave Macmillan, 2016. xxxii + 241 pp.
Keywords: Abel Gance; silent cinema; early sound cinema